IMPLEMENTASI SISTEM INFORMASI SURAT MENYURAT BERBASIS WEB MENGGUNAKAN CODEIGNITER - M. Zakki Abdillah; Erba Lutfina; Ahmad Nugroho; Muhammad Ramdan; Dimas Benyamin (Fakultas Sains dan Teknologi, Universitas Nasional Karangturi, 2023)
One of the administration processes in a university is the correspondence process. The process of managing correspondence at Karangturi National University Semarang still uses a manual process. Manual management processes can lead to high levels of errors. This research is a continuation of previous research on the analysis and design of a web-based letter disposition information system. In previous research, the stages of interviews, data collection, analysis and design of the disposition of the letter were carried out. The discussion in this research is the implementation of web-based correspondence using CodeIgniter. The results of implementing this information system can be accessed online and in real time, because this information system is web-based.